2010
DOI: 10.1111/j.1532-950x.2010.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and In Situ Application of an Adjustable Aiming Device to Guide Extra‐ to Intraarticular Tibial Tunnel Drilling for the Insertion of the Cranial Cruciate Ligament in Dogs

Abstract: The proposed technique may reduce tibial tunnel misplacement when performing intraarticular CCL repair using a tibial bone tunnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
19

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 51 publications
1
6
0
19
Order By: Relevance
“…It should be noted; however, that there was a large standard deviation in this measurement (>50% change in either direction). A study performed by Winkels et al showed the mediolateral position of the tibial insertion was relatively constant, but the craniocaudal position was associated with tibial depth. We looked only at the craniocaudal position of the CrCL‐Li and the large standard deviation in our results supports Winkels previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted; however, that there was a large standard deviation in this measurement (>50% change in either direction). A study performed by Winkels et al showed the mediolateral position of the tibial insertion was relatively constant, but the craniocaudal position was associated with tibial depth. We looked only at the craniocaudal position of the CrCL‐Li and the large standard deviation in our results supports Winkels previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Acredita-se que a razão pela qual as técnicas intra-articulares em cães, especialmente aquelas que fazem uso de túneis ósseos, falham em restaurar a cinemática normal do joelho pode estar relacionada com a escolha imprópria do enxerto e confecção incorreta na posição dos túneis (2,10,14) . Muitas variações quanto a confecção dos túneis ósseos e fixação do enxerto foram realizadas, porém sem um padrão estabelecido (2,6,15) .…”
Section: Introductionunclassified
“…Muitas variações quanto a confecção dos túneis ósseos e fixação do enxerto foram realizadas, porém sem um padrão estabelecido (2,6,15) . Em cães, atualmente, os pesquisadores têm procurado refinar e aperfeiçoar a técnica de reconstrução intracapsular do LCCr (2,7,14,15,16,17,18) . Estas sugerem que a reconstrução anatômica do enxerto do LCCr pode ser uma abordagem promissora para restaurar a estabilidade normal e cinemática articular (14,18) .…”
Section: Introductionunclassified
“…No established treatment restores normal stifle kinematics, and clinical success varies among stifle stabilization procedures . Current research suggests that anatomical CrCL graft reconstruction may be a promising approach to restore normal joint stability and kinematics …”
Section: Introductionmentioning
confidence: 99%
“…Canine CrCL reconstruction has limited acceptance in the surgical community due to difficulties with graft harvest, viability, placement, and attachment, in addition to variable graft behavior . Further, canine CrCL reconstruction techniques have been associated with higher complication rates than osteotomy and extra‐capsular stabilization .…”
Section: Introductionmentioning
confidence: 99%